Raymond Suttner, Inside Apartheid’s Prison (Historia, 2021)
The updated edition of Raymond Suttner’s Inside Apartheid’s Prison is a timely reminderof how unromantic and painful the struggle was for those enlisted to join in the struggleagainst apartheid. Moreover, the book reminds all South Africans that the fight againstapartheid or any other injustice is one that will have various facets and faces, even inthe form of a white middle class lecturer. Yet, two facets of the books keep that keep italluring are its open discussion concerning the unglamorous and sometimes painfulconsequences of the fight against the National Party’s Apartheid system.
Keywords: Raymond Suttner; apartheid; Prison; South Africa; National Party